Bacterial susceptibility changes post national shortage of first cephalosporin in Japan: a longitudinal retrospective database study using interrupted time series analysis. (September 2022) - Miyamori, Daisuke; Kamitani, Tsukasa; Kashiyama, Seiya; Ito, Masanori; Ohge, Hiroki; Yamamoto, Yosuke
Highlights: A quasi-experimental study using a large-scale registry of AMR measures Narrow-spectrum antimicrobial agent shortage led to changes in susceptibility Susceptibility to cefazolin improved in Gram-negative rod bacteria Switching narrow-spectrum antimicrobial agents may effective Abstract: Objectives: The clinical evidence for the effect of narrow-spectrum antimicrobial shortages on bacterial susceptibility is limited. Our purposes were to determine the affects of the disruption of most of the cefazolin (CEZ) supply in Japan on the susceptibility of pathogens and to analyze how long these changes persisted after the shortage of CEZ. Methods: We performed an interrupted time series analysis using the Japanese Infectious Disease Nationwide database. We analyzed each pathogen before and after CEZ shortage in 52 university hospitals from 2018 to 2020. May to November 2019 was designated as the implementation term for CEZ shortage. The primary outcome was the susceptibility to CEZ and other antimicrobial agents. Amongst all pathogens isolated from facilities, we identified pathogens that were tested for susceptibility to CEZ. Results: Of the 26 pathogens identified, analysis was performed on a total of 36, 346 isolates of five pathogens ( Escherichia coli, Klebsiella pneumoniae, Klebsiella oxytoca, Proteus mirabilis, and Staphylococcus aureus ). Amongst four Gram-negative pathogens with low susceptibility, there were no significant immediate changes after the CEZ shortage; however, the slope change significantly increased by 1.29 to 2.69% per month and continued to improve one year after the shortage. Regarding S. aureus, which was highly susceptible at the baseline, neither immediate change nor slope was significant. Conclusion: This quasi-experimental analysis using a nationwide-large database revealed that restriction of use because of narrow-spectrum antimicrobial shortages may lead to improved susceptibility over the subsequent year. The results suggest that temporary switching of antimicrobial agents on a national scale could be effective.